2022
DOI: 10.1177/17479541221094670
|View full text |Cite
|
Sign up to set email alerts
|

Selected factors for triple jump preparation: A case study of an Olympic silver medalist

Abstract: The People's Republic of China obtained at the 2020 Tokyo Olympic Games its best historical performance in the triple jump, thereby winning the silver medal. The objective of this case study was to present how evidence-based knowledge was applied to improve selected factors that may have contributed to this result. The factors included running speed, strength, muscle power, jumping technique, body composition, mental preparation, training organization, and recovery. Short training blocks, monitoring of trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The relationship between approach speed and performance in both jumps is positive and significant. However, the correlation values are higher in the long jump ( Moura et al, 2005a ), suggesting a more significant number of determining factors in the triple jump ( Hutt, 1989 ; Moura et al, 2023 ). Hay (1993) demonstrated that when studying athletes who participated in both events, approach speeds were higher in the long jump, which strengthens the understanding that it is the characteristics and demands of the events and not necessarily the athletes’ abilities that are responsible for the reduced values of approach speed in the triple jump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between approach speed and performance in both jumps is positive and significant. However, the correlation values are higher in the long jump ( Moura et al, 2005a ), suggesting a more significant number of determining factors in the triple jump ( Hutt, 1989 ; Moura et al, 2023 ). Hay (1993) demonstrated that when studying athletes who participated in both events, approach speeds were higher in the long jump, which strengthens the understanding that it is the characteristics and demands of the events and not necessarily the athletes’ abilities that are responsible for the reduced values of approach speed in the triple jump.…”
Section: Discussionmentioning
confidence: 99%
“…For each event (training or competition), the standard deviation of this distance for each step is calculated, indicating the accumulated error in that step. Our study measured running variability in the last six steps ( Moura et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Triple jumping has very high loading on the body, approaching 16 times body weight on a single leg [ 29 ]. This high loading means that the number of full approach triple jumps that are completed in a season is limited [ 30 ]. It is possible that triple jump athletes chose to limit their competitions to major events and take longer periods of time from competition.…”
Section: Discussionmentioning
confidence: 99%